Marxismo ecosocialista - Blanco Martín, Carlos Javier (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
Marx’s theory and Marxist praxis are inscribed inside a Materialistic Natural Philosophy, that coincide in a great extent with our actual Ecological view of Nature and Society. The evolutionist and dialectical view of Nature and History is to be the frame of an Ecosocialist vision and praxis: the present response to Ecological Imperialism.